Response to Osimertinib in a Patient with Non-Small Cell Lung Cancer and Two Uncommon *EGFR* Mutations - Christoforos Astaras; Adrienne Bettini; Daniel C. Betticher (healthbook TIMES. Oncology Hematology)
In advanced non-small cell lung cancer (NSCLC), epidermal growth factor receptor (*EGFR*) mutations are one of the most frequent oncogenic drivers. They confer a favorable prognosis and strongly predict sensitivity to EGFR tyrosine kinase inhibitors (TKIs). Over the last decades, several *EGFR* genetic alterations, common and uncommon mutations, have been described in exons 18−21. Common mutations are exon 19 deletions (most frequently E746-A750) and exon 21 L858R substitution. Uncommon mutations include exon 18 G719X, exon 20 S768l, exon 21 L861Q and many other rare ones. This report describes the case of a 55-year-old woman with a newly diagnosed metastatic lung adenocarcinoma harboring two rare *EGFR* mutations and showing sustained response to osimertinib.